Variability in Urediniopustule and Urediniospore Size of Melampsora ciliata on Poplar Genotypes - Sharma, Sanjeev; Sharma, R. C.; Gupta, A. K. (Indian Forester, 2006)
Variation in the dimensions of urediniopustules and urediniospores of Melampsora ciliata produced on different popular species/cultivars/clones/hybrids has been observed in the present investigations. Smallest urediniopustules were produced on P.deltoides ’Lux’ (0.38 mm) while largest on P.yunnanensis (1.34 mm). In P.ciliata clones/hybrids, smallest urediniopustules were recorded in 53M1 (0.16 mm) while largest in Chhatrari (0.90 mm). Largest spore size (33.6 Ã— 16.3 Î¼m) was recorded on P.deltoides ’Lux’ and 64M1 (36.3 Ã— 17.3 Î¼m) while smallest on P. xeuramericana ’Robusta AE’ and 53M1. Irrespective of species/cultivars, urediniospore size ranged from 13.1-39.3 Ã— 13.1- 19.6 Î¼m. The average urediniospore size of M.ciliata produced on P.ciliata clones ranged from 30.8 -36.3 Ã— 15.4 - 17.1 Î¼m while that on hybrids from 27.2 - 36.3 Ã— 14.5 - 20.0 Î¼m.